(38) An Introductory Note Operation Research مذكرة تمهيدية حول بحوث العمليات - Mohamed Dessouki (معهد التخطيط القومي, 2018)
This study aims to show the history , types and characteristics of operation research on the one hand. On the other hand, it represents operation research steps and its applications.